Effects of river width on sleeping-site selection by proboscis monkeys (Nasalis larvatus) in Sabah, Malaysia - Henry Bernard; Ikki Matsuda; Goro Hanya; Abdul Hamid Ahmad (Universiti Malaysia Sabah, 2011)
Previous studies have suggested that Proboscis monkeys sleep in trees located by riverbanks and cross rivers at their narrower points effectively avoid land-based and aquatic-based predators.